Analysis of Government Regulation in Lieu of Law (PERPPU) No 1 of 2020 Implementation on Income Tax Payable in Overcoming Financial Complication During the Covid-19 Pandemic (Case Study on CV KP) - Ida Ayu Nyoman Widyastini; Nyoman Sentosa Hardika; I Nyoman Mandia (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This study aims to compare the income tax payable and income tax 25 due to the adjustment of the corporate income tax rate payable on CV KP which is a corporate taxpayer affected by the Covid-19 pandemic who undergoes the adjustment of the corporate income tax rate based on PERPPU No. 1 of 2020. The data collection technique used was documentation technique with comparative descriptive data analysis techniques. The results showed that a 22% rate adjustment application result in relief of IDR 27.419.811,00 obtained by CV KP. The amount of income tax 25 by a 22% rate application and tax incentives in 2020 is IDR 15,266,362.00 for the April-June and the July-December is IDR 10,904,544.00, and income tax 25 in 2021 obtained relief of IDR 7. 739,900.00 for the period from April to June while the period from July to December returned to Rp. 15,479,801.00. CV KP should be able to save cash dibursement in 2020 during the Covid-19 pandemic to maximize the rate adjustment so that it does not cause a large overpayment. Thus, CV KP should make a separate calculation in determining the amount of income tax 25 by a 20% rate for the current year 2022.